2020
DOI: 10.1002/14651858.cd012547.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver involvement in interventions for improving children's dietary intake and physical activity behaviors

Abstract: Caregiver involvement in interventions for improving children's dietary intake and physical activity behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 161 publications
2
29
0
4
Order By: Relevance
“…Consistent with our findings, Ismail and colleagues also highlight the importance of parental engagement for the success of school based dietary interventions [ 14 ]. Literature more widely recognizes the significant role of parents in shaping family, and thus, child eating practices [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Ismail and colleagues also highlight the importance of parental engagement for the success of school based dietary interventions [ 14 ]. Literature more widely recognizes the significant role of parents in shaping family, and thus, child eating practices [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a significant proportion of preschool-aged children do not meet this target (less than 50% across studies) [ 7 ]. Several interventions designed to increase PA or reduce sedentary behaviors (eg, limit screen time) have resulted in inconsistent findings [ 10 - 12 ]. According to a meta-analysis of intervention studies with preschool-aged children, only small to moderate effects have been observed for improving PA, suggesting room for improvement in achieving the desired outcomes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, less than 1/3rd of dietary behavior guidelines recommended some form of parent engagement strategy. Despite mixed evidence surrounding the impact of parent involvement on child diet [78,79], there is some suggestion that involvement of parents particularly around the packing of childcare lunchboxes can improve vegetable intake [80].…”
Section: Discussionmentioning
confidence: 99%